Communication undergraduate degrees: between the search for excellence, the conceptual ambiguity and the market dictatorship - Eiró-Gomes, Mafalda (Journal of Management and Business Education, 2021)
We’ll argument in this paper that the area of undergraduate studies that we can consider as belonging to the great area of the communication sciences and, in particular, those areas that have as one of their purposes also the professional training in Corporate Communications / Public Relations, seem to be navigating in a blurriness of both theoretical constructs and purposes, as well as a lack of public recognition. Moreover, it will be argued that the main purpose underlying all definitions should be the old idea from the Enlightenment that the mission of undergraduate studies is, before and above all, the shaping of rational and responsible citizens.